2022
DOI: 10.1002/pc.26890
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing surface insulation of glass fiber reinforced polymer composites by plasma fluorinating glass fiber

Abstract: Glass fiber reinforced polymer (GFRP) is a widely used composite material in industrial production. In this article, glass fiber (GF) was fluorinated by dielectric barrier discharge (DBD), and the GFRP composites made of GF with different fluorination time and various numbers of fluorinated GF layers were prepared to improve the surface insulation property. The effect of plasma fluorination on GF was analyzed by scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS), including the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The peak at 916 cm −1 gradually disappeared, indicating epoxy groups were reacted with the increased amount of PEI. The chemical compositions of GFs were further determined by C1s XPS and the outcomes are displayed in Figure 1C–F and surface elements analysis of GF samples are presented in Table S1 34,35 . The peaks at 284.5, 286.3 and 288.7 eV had been ascribed to CC, CO, and CO bonds 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 916 cm −1 gradually disappeared, indicating epoxy groups were reacted with the increased amount of PEI. The chemical compositions of GFs were further determined by C1s XPS and the outcomes are displayed in Figure 1C–F and surface elements analysis of GF samples are presented in Table S1 34,35 . The peaks at 284.5, 286.3 and 288.7 eV had been ascribed to CC, CO, and CO bonds 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical compositions of GFs were further determined by C1s XPS and the outcomes are displayed in Figure 1C-F and surface elements analysis of GF samples are presented in Table S1. 34,35 The peaks at 284.5, 286.3 and 288.7 eV had been ascribed to C C, C O, and C O bonds. 36 After the treatment of GFs with cross-linking modified sizing agent, the C1s spectra of GF-1, GF-6, and GF-12 showed characteristic peak at 285.4 eV (C N), 37,38 which indicated the successful introduction of PEI.…”
Section: The Treatment Of Gfs With Crosslinking Sizing Agentmentioning
confidence: 99%
“…The elemental F content on the surface of the fluorinated Al 2 O 3 /EP samples increased significantly, up to 12.38%. The C1s peaks of the untreated Al 2 O 3 /EP, APPJ‐F‐3, and APPJ‐F‐5 were split, as shown in Figure 5(A)~(C), to study the presence form of the F element created on the surface of the Al 2 O 3 /EP 27 . It was found that the C1s peaks of the untreated Al 2 O 3 /EP could be divided into three peaks, while the C1s peaks could be divided into more peaks after plasma fluorination, and the peaks of each peak were not the same.…”
Section: Resultsmentioning
confidence: 99%
“…Glass fiber‐reinforced polymers are composite materials widely used in industrial production. [ 17 ] Ghanbari et al found that including glass fibers (GF) at 23°C significantly improved the heat distortion temperature (HDT), flexural modulus, and tensile strength of the material. [ 18 ] Similarly, Zhao et al observed considerable enhancement of the mechanical properties of the composite as the content of high‐performance glass fibers increased, especially when four bundles of GF were added, with a nylon56/GF composite reaching a tensile strength of 160 MPa, which was 86.9% higher than that of nylon56.…”
Section: Introductionmentioning
confidence: 99%